EXHIBIT C - LINENBERGER,OJ (Tufts Archival Research Center, 2007)
Letter from the Deputy City Manager James Linenberger to Leo C. Middendorf the labor relations representative to the San Mateo Fire Department acknowledging that he received a letter referred to by Mr. Delong.